2016
DOI: 10.1002/jgt.22052
|View full text |Cite
|
Sign up to set email alerts
|

The Monochromatic Circumference of 2‐Edge‐Colored Graphs

Abstract: Li et al. (Discrete Math 310 (2010), 3579–3583) asked how long the longest monochromatic cycle in a 2‐edge‐colored graph G with minimum degree at least c|V(G)| could be. In this article, an answer is given for all c∈(0,1) to an asymptotic form of their question.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…, and let G be a graph on n ≥ n 0 vertices with δ(G) ≥ (3/4 + γ)n. Apply Lemma 5.1 to G to get a balanced bipartite (ǫ, d)-reduced graph Γ on 2k vertices with minimum degree at least (3/4 + γ/2)k and then apply Theorem 4.2 to Γ. If Γ has a monochromatic connected matching of size at least (1/2 + 2η)k, then apply Lemma 5.4 to get a cycle of length at least (1 + η)n. Otherwise, Γ is 4η-extremal, so by Lemma 7.1, G is 8η-extremal and since 16 √ 8η ≤ 64 √ η ≤ γ we may apply Proposition 8.5 to G to finish the proof.…”
Section: Stabilitymentioning
confidence: 98%
See 1 more Smart Citation
“…, and let G be a graph on n ≥ n 0 vertices with δ(G) ≥ (3/4 + γ)n. Apply Lemma 5.1 to G to get a balanced bipartite (ǫ, d)-reduced graph Γ on 2k vertices with minimum degree at least (3/4 + γ/2)k and then apply Theorem 4.2 to Γ. If Γ has a monochromatic connected matching of size at least (1/2 + 2η)k, then apply Lemma 5.4 to get a cycle of length at least (1 + η)n. Otherwise, Γ is 4η-extremal, so by Lemma 7.1, G is 8η-extremal and since 16 √ 8η ≤ 64 √ η ≤ γ we may apply Proposition 8.5 to G to finish the proof.…”
Section: Stabilitymentioning
confidence: 98%
“…Finally we state the lemma which allows us to turn the connected matching in the reduced graph into the cycle in the original graph. Some variant of this lemma, first introduced by Luczak [13], has been utilized by many authors, in particular [8], [2], and [16]. See Lemma 2.2 in [2] for the variant of Luczak's lemma which is used to build the nearly spanning paths in each pair (in place of the much stronger blow-up lemma).…”
Section: Regularity: From Connected Matchings To Cyclesmentioning
confidence: 99%
“…(White [14]) Let G be a graph of order n such that for some integer m 3, δ(G) 2m−1 m 2 n. If the edges of G are 2-colored then there is a monochromatic component of order at least n m−1 . This result is basically implicit in the proof of Lemma 4.7 in White [14] (see also in [15]); however, it is not even stated there as a separate statement. Note that Theorem 4.1 is false for m = 2, in which case Lemma 1.1 gives the order of the largest monochromatic component.…”
mentioning
confidence: 99%
“…|A 123 | > N/4.Proof. For A 12 = ∅ the assertion follows from(14). If A 12 = ∅, then, by (15) and Claim 26, we get|A 123 | = N − |A 1 | − |A 2 | − |A 3 | − |A 12 | > N/4 .Let us also note the following consequence of Claim 26.Claim 28.…”
mentioning
confidence: 83%
“…Schelp [12] observed that for sparse graphs H, such as paths or cycles, we may expect that G → (H) r for all G which have R r (H) vertices, provided the minimum degree of G is large enough. For H which is a path or a cycle and just two colours this problem has been thoroughly studied in a series of papers (see [1,6,9,13,14]), so now we know the minimum value of the constant c for which, in the relation K N → (C n ) 2 , the complete graphs K N can be replaced by G with δ(G) ≥ cN , at least for large n. Not surprisingly, the optimal constant c depends on the parity of n.…”
Section: Introductionmentioning
confidence: 99%